(untitled) (Journal of Life and Earth Science, 2011)
Monthly variations of the physicochemical parameters in some selected water bodies (12 Beels and 210 ponds) in Natore during July 2006 and June 2007 have been studied. The highest values for water temperature, alkalinity, ammonia, free CO2, DO, pH and total hardness in Beel waters were 31.5°C (May ’07), 180ppm (January and February ’07), 2.5ppm (September ’06), 9.6ppm (April ’07), 7.5ppm (January ’07), 8.6 (December ’06) and 190ppm (February ’07), respectively and the lowest values were 15°C (February ’07), 35ppm (October ’06), 0.5ppm (December ’06), 6.3ppm (January ’07), 4.8ppm (April ’07), 6.8 (September ’06) and 50ppm (September ’06), respectively. The highest and lowest values of these parameters in pond waters were 33°C (May ’07), 200ppm (March’07), 2.3ppm (July ’06), 9.3ppm (April ’07), 7.5ppm (January ’07), 8.6 (November ’06) and 200ppm (February ’07) respectively, and 17°C (December ’06), 50ppm (October ’06), 0.6ppm (December ’06 and January ’07), 6.4ppm (January ’07), 5.0ppm (May ’07), 6.2 (April ’07) and 40ppm (September ’06) respectively. Changing in water quality parameters resulted in a stress response in the fishes, making them more susceptible to parasitic attacks and diseases, many of them being fatal. Key words: Beels; ponds; water quality parameters; fish diseases DOI: 10.3329/jles.v2i2.7493 J. Life Earth Sci., Vol. 2(2) 27-30, 2007